(untitled) (Journal of Economic Research & Business Administration, 2016)
In the state power and attitude about her are the main elements form-ing the political system. The state as a part of society’s political system and the particular organization of political power is characterized by the ability to influence the activity of people of various state institutions, institution-alize and give it the power of obligatory character. These are the Institute and the Institute is a public service. Special structural organization, called the state apparatus is a system of state bodies, interconnected by common principles, objectives, endowed with power and possessing the material and technical means to carry out its functions.